A study of adverse cutaneous drug reactions in the department of dermatology of a teaching hospital in Jamnagar, India - Dhanani, Jagruti G.; Sukhlecha, Anupama (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Adverse drug reactions cause significant morbidity and mortality in health care set up. They are responsible for a significant number of hospital admissions. The data for adverse cutaneous drug reactions (ACDRs) is limited our country. Thus, the present study emphasises on the need of an effective adverse drug reaction reporting programme. Methods: A prospective study to assess the ACDRs in Dermatology department was conducted in a teaching hospital of India. Male to female ratio, most common class of drug, individual drugs causing ACDRs, common types of ACDRs were studied. Other parameters like causality assessment, preventability and seriousness of ACDRs were also studied. Results: A majority of the patients (38%) with ACDR were in the age group of 25-44 years followed by 45-64 years (31%). The rate of ACDRs was more in males (54%). The most frequent ACDR reported was maculopapular rash (38%), followed by urticaria (19%) and fixed drug eruptions (12%). Most of the reactions (93%) were bizarre/ unpredictable in nature. Amongst drug groups, antimicrobials (48%) were most frequently associated with ACDRs followed by NSAIDs (30%) and antiepileptics (12%). Most of the reactions (94%) were mild-moderate in nature. Only 9% of ACDRs reported in this study were preventable. Paracetamol was the most common offending drug followed by cotrimoxazole, ibuprofen, amoxicillin, phenytoin in decreasing order. Causality assessment found ACDRs in probable category (68%) using WHO-UMC criteria. Conclusions: It is important to monitor and report adverse drug reactions in order to promote safe and rational use of medicines.